A motion analysis of work-rate & heart rate of elite Kuwayti handball players - AI-Lail, A. A. (Education. Physical training. Sport)
Eight elite male handball players from Kuwait clubs were filmed while competing in the handball league in Kuwait during 1996. Filming was done aver eight handball matches far determination of work rate profiles. The aim of this study was to establish a motion activity profile of handball play. There were eight activities analysed, with the ball and without the ball. These activities were walking, jogging, striding, sprinting, moving sideways, and walking. Data were thus provided on mean (+ SD) of the total time covered far each 30 mm period in each activity, total distance covered at each activity and frequency of each event. The overall time for each type of activity with or without the ball was calculated. Analysis was also linked to a total distance covered far each activity. The total distance covered during the handball match was 2478 ± 224 m with and without the ball; this distance which players covered consisted of walking 620 m, jogging 707 m, striding 158 m and sprinting 451 m, and the total actual time when the player was an the playing court was approximate 40 ± 7.2 mm. The players spent a long time in walking activity (21.3 ± 5.4 mm) both with and without the ball, and the percentage of the total time walking was 53.9%. Also the percentage of the total time jagging was 14.9% of the actual match time, although the high intensity activities (striding and sprinting) made up 2% and 3.8% respectively of the total actual match play time. Utility movements accounted far 25.3% of the total time. The high-intensity activities (striding and sprinting) made up 2% and 3.8% of the time based activity profile far handball and 5.4% and 2.2% far soccer (Reilly 1994b). However, event changed in handball once every 5.7s but in soccer every 3.1s. The players heart rate of 136 ± 5 beats.min-1 and 143 ± 6 beats.min-1 during training and match respectively suggest that the physiological response induced during match is higher than that during training. The findings have implication far coaches with regard to the organisation of training drills for handball.